Suspicious Activities and Anomaly Detection in Surveillance Video Using Multiple Instance Learning Techniques - Baby, M. Petchiammal; Jeyalakshmi, T. Ratha (International Journal of Computer Sciences and Engineering, 2025)
Surveillance videos are proficient to detain a diversity of sensible anomalies. In this work, we advise to find out anomalies by comparing both normal and irregular videos. To remain on away from annotating the irregular segments or clips in training videos, which is very time overwhelming, we recommend to learn anomaly during the deep multiple case position framework by stage averaging weakly labeled direction videos, i.e. the training labels are at video level instead of clip-level. In our approach, we think normal and anomalous videos as bags and video segments as instances in multiple instance learning (MIL), and mechanically learn a deep anomaly location form that predicts high anomaly scores for anomalous video segments. Furthermore, we begin sparsity and temporal softness constraints in the ranking loss function to improved localize anomaly during training. We also set up a new large-scale first of its kind dataset of 128 hours of videos. It consists of 1900 long and untrimmed real-world surveillance videos, with 13 practical anomalies such as fighting, road accident, burglary, break-in, etc. as well as normal activities. This dataset can be used for two tasks. First, general irregularity detection considering all anomaly in one group and all normal activities in another group. Second, for recognizing each of 13 abnormal actions. Our investigational consequence clarify that our MIL performance for anomaly detection achieves significant development on anomaly detection act as compared to the state-of-the-art Techniques. We present the consequences of several current deep learning baselines on anomalous action recognition. The low detection presentation of these baselines finds that the dataset taken is very hard and opens extra opportunities for opportunity work